PENDAMPINGAN AUTOMASI PENYUSUNAN LAPORAN KEUANGAN - Achmad Syaiful Hidayat Anwar; Firda Ayu Amalia; Tri Wahyu Oktavendi (Universitas Muhammadiyah Malang, 2021)
Non-profit businesses also need financial reports as a tool for making decisions. The first problem related to financial reporting at SMK Negeri 2 Batu is that the current financial reports are not systemized and recording is still manual. The proposing team tries to make improvements related to financial reporting problems faced by partners. It is hoped that with the financial reporting system being more compatible with accounting standards, the resulting financial reports will be of higher quality. The proposer is able to solve these problems by using stages, namely: Problem Identification Stage, Financial Reporting Application System Design Stage, System Implementation Stage, and Evaluation Stage. As a result, financial reporting problems can be solved by creating financial reporting applications. Financial reporting becomes more reliable and on time. Subsequent financial reporting can be in the form of application software on mobile phones, so that users can access it anywhere. The implication of this activity is that the automation of financial reporting can have an impact on the speed and accuracy of decision making. The benefits obtained by partners are in the form of effectiveness and efficiency in making financial reports.